Teen Spirit : How Adolescence Transformed the Adult World - Howe, Paul, 1966- (Book collections on Project MUSE., 2020)
"Teen Spirit argues that many social trends in modern society, both negative and positive, ultimately stem from the emergence of a more sharply defined teenage stage of life in the early years of the twentieth century and the gradual entrenchment of adolescent character traits in rising generations"--